ENERGY EFFICIENT SENSED DATA CONVEYANCE FOR SENSOR NETWORK UTILIZING HYBRID ALGORITHMS - Raj, Jennifer S. (IRO Journal on Sustainable Wireless Systems, 2019)
The wireless sensor networks incorporated with multitude of distributed autonomous sensors with the potency of monitoring any changes that is physical or environmental, faces few challenges due to its distributed nature and the limited battery availability. The challenges incurred result with delay in the transmission, dynamic topology changes, and the link failures due to the reduced life span of the sensors. The researchers claim that the reduce in the life span of the sensor are the result of energy usage in the transmission leading to an enormous battery power consumption for a single conveyance. So the paper proposes an energy efficient conveyance for the information that are sensed utilizing the hybrid algorithms that include the K-means for the purpose of clustering, Genetic algorithm for the purpose of cluster head selection and the Ant colony optimization for determining the shortest path between the member to the cluster head and the cluster head to the base station. The performance evaluation of the proposed process using the network simulator-2 serves as an evidence for the improved capabilities of the same in terms of the throughput, packet delivery ratio (PDR), energy efficiency and the network life time.